V for Voice: Strategies for Bolstering Communication Skills in Statistics. Issue 2 (4th May 2017) - Khachatryan, Davit; Karst, Nathaniel
ABSTRACT: With the ease and automation of data collection and plummeting storage costs, organizations are faced with massive amounts of data that present two pressing challenges: technical analysis of the data themselves and communication of the analytics process and its products. Although a plethora of academic and practitioner literature have focused on the former call, the latter challenge has received less attention. Here, we present strategies that we have found effective for bolstering communication skills of both undergraduate students and masters candidates at a business school. These approaches are based on the case studies that provide ample opportunity for oral communication among students with strong backgrounds in mathematics and introductory statistics, and solid training in written communication among student populations with less homogeneous preparation. We provide detailed discussions motivated by concrete examples executed across three courses.